The Role of Sustainability Reporting in the Disclosure of Non-Financial ESG Information: a Case Study of a Construction Company - Drozd, Andżelika (Olsztyn Economic Journal, 2025)
Sustainable development has become a key paradigm of modern management, reflected both in corporate strategies and in reporting practices. The aim of the article is to discuss the concept, origins, and essence of ESG reporting, analyse EU and national regulations, and evaluate the 2024 sustainability report of Budimex Group. The company was selected based on the Build the Future ranking, carried out by Builder magazine, PwC Poland, and Dun & Bradstreet Poland, in which Budimex ranked first among general contractors. The study focused on environmental, social, and corporate governance disclosures. The analysis leads to the conclusion that the Budimex Group’s ESG report serves primarily an informational function, while its analytical potential could be strengthened by a stronger link between indicators and measurable, realistic and verifiable strategic goals, which would enable a reliable assessment of the effectiveness of ESG activities. The research was based on a qualitative method – a case study.